Selective CD28 Blockade Results in Superior Inhibition of Donor‐Specific T Follicular Helper Cell and Antibody Responses Relative to CTLA4‐Ig. Issue 1 (14th August 2017) - Badell, I. R.; La Muraglia, G. M.; Liu, D.; Wagener, M. E.; Ding, G.; Ford, M. L.
Abstract : Donor‐specific antibodies (DSAs) are a barrier to improved long‐term outcomes after kidney transplantation. Costimulation blockade with CTLA4‐Ig has shown promise as a potential therapeutic strategy to control DSAs. T follicular helper (Tfh) cells, a subset of CD4 + T cells required for optimal antibody production, are reliant on the CD28 costimulatory pathway. We have previously shown that selective CD28 blockade leads to superior allograft survival through improved control of CD8 + T cells relative to CTLA4‐Ig, but the impact of CD28‐specific blockade on CD4 + Tfh cells is unknown. Thus, we identified and characterized donor‐reactive Tfh cells in a murine skin transplant model and then used this model to evaluate the impact of selective CD28 blockade with an anti‐CD28 domain antibody (dAb) on the donor‐specific Tfh cell–mediated immune response. We observed that the anti‐CD28 dAb led to superior inhibition of donor‐reactive CXCR5 + PD‐1 high Tfh cells, CD95 + GL7 + germinal center B cells and DSA formation compared with CTLA4‐Ig. Interestingly, donor‐reactive Tfh cells differentially upregulated CTLA4 expression, suggesting an important role for CTLA4 in mediating the superior inhibition observed with the anti‐CD28 dAb. Therefore, selective CD28 blockade as a novel approach to control Tfh cell responses and prevent DSA after kidney transplantation warrants further study. Abstract : The authors examine the impact of selective CD28 blockade on the T follicular helper cell subset in a murine skin transplant model and report that donor‐specific T follicular helper cell–mediated responses are superiorly inhibited by a selective anti‐CD28 dAb compared to costimulation blocked with CTLA4‐Ig.